Legal Aspects of Dual-Use Technologies: Emerging and Disruptive Technologies - Székely, János (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
This chapter aims to address the problem presented by governance regimes applicable to the dual (civilian and military) use of emerging and disruptive technologies such as artificial intelligence and biotechnology. The author first examines the definition of “dual use” as it emerges from various unilateral and multilateral governance instruments. As several definitions currently coexist, “dual use” is found to constitute a fuzzy notion, requiring clarification in further regulation and application. The major regimes governing dual-use technology proliferation and trade are presented with an emphasis on the role of securitisation in determining the applied regulatory approach and content. The technological and economic rivalry between the United States of America and the People’s Republic of China was found to have a defining role in the current transformation of such governance regimes to the detriment of free trade. Subsequently, the problems posed by artificial intelligence, biotechnology, and 5G broadband data transfer were examined in light of dual-use technology regulation, with conclusions presented regarding the future desirable development of the regulatory environment.Keywords: dual-use, emerging technology, disruptive technology, securitisation, export control.